Penggunaan Container Networking dalam Pengelolaan Infrastruktur Cloud-Native - Mulyana, Nana; Miswanto; Kalsum, Putri Annisa (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
Digital transformation drives organizations to adopt cloud-native technologies to improve efficiency and operational flexibility. Container networking becomes a key element in cloud-native infrastructure management because it enables optimal inter-container communication. This article aims to analyze the role, advantages, barriers, and implementation strategies of container networking within the cloud-native ecosystem. The research method used is descriptive qualitative with a case study approach. The research results show that container networking implementation increases the scalability, reliability, and security of cloud-native infrastructure, despite challenges in network management and data security. This article also proposes an adaptive and innovative container networking management model to enhance operational efficiency in cloud-native environments.